SESERAHAN MENURUT AKTIVIS MUHAMMADIYAH: AKULTURASI BUDAYA DALAM PERNIKAHAN ADAT JAWA - Hikmah Hariyati (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
Indonesia has more than 1,300 tribes with different cultures and of course the wedding procession of each region is also diverse with traditions that have long been maintained until now because of the customs and beliefs they hold. Seserahan is defined as the ability of the prospective husband to the prospective wife in providing physical and spiritual support or some call it a gift for a woman's family. There is no argument that clearly allows or prohibits offerings in the wedding procession because seserahan is a custom that uses 'urf as a benefit which is not legally stipulated in the syara' but is based on the habits of the local community that have been carried out repeatedly. The purpose of this study was to determine the form of cultural acculturation in Javanese traditional weddings in Wates Village, Blitar Regency. This study uses a type of field research (field research) to the community, bride shamans and Muhammadiyah tarjih scholars with a qualitative descriptive approach. The results show that the process that occurs when marriage uses Javanese customs is a result of acculturation of Javanese and Islamic culture in Wates Village, Blitar Regency because there is resistance to local traditions and culture, resulting in Islam versus Kejawen tensions and conflicts. According to activist Muhammadiyah Blitar, there are no problems related to the offering ceremony in Javanese tradition because it is only a symbol to always remember Allah, pray from danger, and the relationship lasts until old age until death picks up. This is all just a form of love for Allah in order to always maintain the marriage relationship.